Concomitant Rupture of Extensor Pollicis Longus and Index Extensor Tendons following Distal Radius Plating—Report of Two Cases and Their Clinical Implication for Tendon Transfer Surgery - Praveen Bhardwaj; Vigneswaran Varadharajan; S Raja Sabapathy (Indian Journal of Plastic Surgery)
Extensor indicis proprius (EIP) tendon transfer is a standard operation for restoration of the thumb extension following rupture of extensor pollicis longus (EPL). In its standard form often the EIP is transferred to the EPL without inspection of the extensor tendons in the fourth compartment and it is retained in its anatomical fourth compartment. However, in a setting of EPL rupture in relation to the distal radius fracture (with or without fixation), concomitant injury to the extensor tendons to the index finger may result in failure of the transfer and even a loss of index finger extension (index finger drop) further complicating the reconstruction and resulting in immense patient dissatisfaction. We herein present two such rare cases to highlight this clinical scenario and how an awareness of this possibility and inspection of the extensor tendons to the index finger before EIP transfer allowed us to prevent this complication. In essence, if we know it, we can prevent it.